Community deployment of metofluthrin emanators to control indoor Aedes aegypti: Efficacy results from a crossover trial in Yucatan, Mexico - Che-Mendoza, Azael; Guillermo-May, Guillermo; Kirstein, Oscar D.; Chi-Ku, Aylin; Pavía-Ruz, Norma; Medina-Barreiro, Anuar; González-Olvera, Gabriela; Devine, Gregor; Vazquez-Prokopec, Gonzalo; Manrique-Saide, Pablo (PLOS Neglected Tropical Diseases, 2025)
Author summary Spatial emanators are an innovative and user-friendly tool for controlling Aedes mosquitoes that transmit viruses such as dengue, chikungunya, and Zika. These devices combine lethal and behavioral effects on mosquitoes and are designed to passively release insecticides into the air at room temperature. These may be suitable for deployment in houses with the aim of creating “bite-free” spaces. By removing the need for conventional application methods, these devices might be rapidly deployed with minimum disruption to households. This study tested the effectiveness of emanators managed by community members versus researchers. In a trial with 588 households, emanators were replaced every three weeks across four cycles. One group of households handled installation and replacement with minimal guidance (“community-led deployment”), while researchers managed these tasks in the other group (“managed deployment”). The groups switched roles after the fourth cycle. The results showed that emanators reduced mosquito numbers by around one-third in both groups. When measuring mosquito bites, emanators reduced bites by up to 94% in the managed deployment group and up to 79% in the community-led deployment group. Importantly, households performed as effectively as researchers. This study shows that emanators can empower communities to protect themselves, making them a valuable tool during outbreaks of mosquito-borne diseases. The results are particularly encouraging given the high rates of insecticide resistance of Ae. aegypti in the study.